Praktik Perkawinan di Bawah Umur di Kabupaten Purwakarta - Dian Qorri Roziah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Amendment to Law Number 1 of 1974 concerning marriage regarding the age limit for marriage into Law Number 16 of 2019 which contains